Mycobacterium tuberculosis Involvement in Tetralogy of Fallot: A Case Report of Tetralogy of Fallot Patient with Pulmonary Tuberculosis in A Tertiary Health Care in Indonesia - Harik Firman Thahadian; Sumardi Sumardi; Eko Budiono (Indonesian Society of Respirology (ISR), 2023)
ckground: Pulmonary tuberculosis in patients with congenital heart disease is a rare case and remains challenging to diagnose and treat. This study aimed to emphasize the association between pulmonary tuberculosis infection and management in patients with congenital heart disease. Case: This case study presents 18-year-old male with Tetralogy of Fallot (ToF) who had pulmonary tuberculosis. The tuberculosis diagnosis was confirmed clinically, followed by positive IGRA. The patient underwent standard care within the hospital and upon discharge, he was prescribed with standard anti-tuberculosis regimen consisting of rifampicin, isoniazid, pyrazinamide, and ethambutol (RHZE) for a week then discontinued it. After 3 months the patient initiated intensive phase (RHZE) for 2 months and followed by 4-month maintenance phase of Isoniazid and Rifampicin. Immediate evaluation showed improved patient’s chest radiography and symptoms’ remission. This study presented provisioning therapy regimen and nutritional care delivery for pulmonary tuberculosis patient with ToF. Further patient’s clinical evaluation suggested a substantial recovery process. The patient prescribed with infection control and dietary management upon hospital discharge. Counseling to improve patient’s knowledge was performed to prevent recurrent TB. Collaborative care established between internal medicine specialists, cardiologist, pulmonologist, and clinical nutritionist appeared to be effective to promote patient’s recovery and quality of life (QoL). Conclusion: Appropriate management of cases improves patient outcomes and QoL. Early screening, diagnosis and treatment should be introduced regardless of the patient’s clinical status. Adequate support from the patient’s family and relatives are required to eliminate TB infection.